2009
DOI: 10.1016/s1472-6483(10)60086-7
|View full text |Cite
|
Sign up to set email alerts
|

CGG repeat sizing in the FMR1 gene in Indian women with premature ovarian failure

Abstract: The CGG repeat stretch in the FMR1 gene is polymorphic, ranging from 5 to 50 repeats in the normal population. Expansion of the repeats to the premutation range (50-200) has been associated with premature ovarian failure (POF). This case-control study was conducted to enumerate CGG repeats in the FMR1 gene in 80 Indian women with non-familial, non-syndromic POF, and 70 controls from the same ethnicity. A possible association between CGG repeats and endocrine profile of these cases was investigated. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
17
1
1
Order By: Relevance
“…In addition, women carrying either alleles with ,28 repeats or alleles with .33 repeats presented with reduced AMH levels, suggesting diminished ovarian reserve in these CGG repeat ranges (Gleicher et al, 2009a). The results of these and a few other studies (Chatterjee et al, 2009;Gleicher et al, 2010a,b;Karimov et al, 2011) suggest that the number of CGG repeats in the normal and intermediate range might also affect the ovarian ageing process over time and thereby the timing of menopause. Therefore, we aimed to investigate the association between the number of CGG repeats in the normal and intermediate range (up to 55 repeats) and age at natural menopause using a large cohort of Dutch post-menopausal women.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, women carrying either alleles with ,28 repeats or alleles with .33 repeats presented with reduced AMH levels, suggesting diminished ovarian reserve in these CGG repeat ranges (Gleicher et al, 2009a). The results of these and a few other studies (Chatterjee et al, 2009;Gleicher et al, 2010a,b;Karimov et al, 2011) suggest that the number of CGG repeats in the normal and intermediate range might also affect the ovarian ageing process over time and thereby the timing of menopause. Therefore, we aimed to investigate the association between the number of CGG repeats in the normal and intermediate range (up to 55 repeats) and age at natural menopause using a large cohort of Dutch post-menopausal women.…”
Section: Introductionmentioning
confidence: 78%
“…275 In another study, the rise in serum concentration of FSH was associated with CGG repeat size within the normal range but exceeding 30 CGGs, both in 80 females with POI and 70 controls. 276 …”
Section: Do the Intermediate Size (Gz) Alleles Cause Abnormal Phenotymentioning
confidence: 99%
“…The frequency of premutation carriers among women with the sporadic form of POI ranges between 1.6% and 3.3% (27,(28)(29)(30)(31) in Caucasian populations, and one study has described a frequency of 4.8% in a group of screened Slovenian patients (32). A study of 80 Indian patients with POI revealed that none of them had CGG repeats within the premutation range (33). The data from these studies and the present study indicate that fewer Asian than Caucasian patients with POI have CGG repeats in the premutation range (11,29,31,32).…”
Section: Figurementioning
confidence: 99%